2023
DOI: 10.37871/jbres1775
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Checklist of Molluscs in the Kelanang Coast at Banting: An Observational Study

Abstract: This research aims to determine the updated species list of molluscs (Gastropods and Bivalves) populating the Kelanang coast at Banting (Selangor) in November 2022. Nine gastropod species and eight bivalve species were discovered in this study, with Pisania striata, Cominella quoyana, and Mereterix casta as the dominant species. This preliminary investigation could provide a continuous baseline for future taxonomical and biodiversity references as part of our efforts to develop coastal marine ecosystem managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…To maintain the coastal environment in Negeri Sembilan, the current study on the benthic organisms (mainly molluscs) found at Sungai Rambai and Pasir Panjang Jetty in Peninsular Malaysia has provided signi icant updated information [34][35]. First, the current list of benthic organisms may be used as a starting point for references with future biomonitoring studies that are comparable to or connected to them [31][32]. Second, the list may be used to choose prospective biomonitors for investigations on ecotoxicology [9,[31][32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To maintain the coastal environment in Negeri Sembilan, the current study on the benthic organisms (mainly molluscs) found at Sungai Rambai and Pasir Panjang Jetty in Peninsular Malaysia has provided signi icant updated information [34][35]. First, the current list of benthic organisms may be used as a starting point for references with future biomonitoring studies that are comparable to or connected to them [31][32]. Second, the list may be used to choose prospective biomonitors for investigations on ecotoxicology [9,[31][32].…”
Section: Discussionmentioning
confidence: 99%
“…First, the current list of benthic organisms may be used as a starting point for references with future biomonitoring studies that are comparable to or connected to them [31][32]. Second, the list may be used to choose prospective biomonitors for investigations on ecotoxicology [9,[31][32]. This often entails measuring the number of microplastics in these benthic mollusks as well as chemical contaminants (or newly developing pollutants).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation